Contraceptive Use, Access to Methods, and Program Efforts in Urban Areas - Ross, John A. (Frontiers in Global Women's Health, 2021)
Based on the latest surveys in 87 countries, urban patterns of contraceptive use, access to methods, and fertility, are analyzed. Urban areas show higher use of contraception and lower fertility rates than rural areas, and the method mix of methods differs. Urban women tend more toward the long term methods of the IUD, implant, and sterilization, and less toward short term, resupply methods. Overall use rises with education and with higher wealth quintiles. By regions, contraceptive use is most unbalanced between urban and rural sectors (highest ratio of urban to rural use ) in sub-Saharan Africa, where the overall levels of use are lowest. Overall, the urban fertility rate is only 70% of the rural rate. Across the 87 countries, the fertility rate correlates negatively with the contraceptive use rate. National family planning programs tend to raise contraceptive use and to improve access to the methods. About half of unmarried, sexually active women use contraception, with great diversity of which method is preferred among countries. That holds for all married women as well: regions and countries show quite different patterns of use; hence planners and donors should focus on the circumstances in individual countries.